2017
DOI: 10.1002/ptr.5822
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory Activity of Cinnamon (Cinnamomum zeylanicum) Bark Essential Oil in a Human Skin Disease Model

Abstract: The effect of cinnamon (Cinnamomum zeylanicum) bark essential oil (CBEO) on human skin cells has not been elucidated. Therefore, we investigated the activity of a commercially available CBEO in a validated human dermal fibroblast system, a model of chronic inflammation and fibrosis. We first evaluated the impact of CBEO on 17 protein biomarkers that play critical roles in inflammation and tissue remodeling. The impact of CBEO on genome‐wide gene expression was also evaluated. CBEO showed strong anti‐proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 20 publications
1
52
1
Order By: Relevance
“…Additionally, we found Cinnamon bark, Syzygium aromaticum, Allspice and Bandit "Thieves" showed excellent activity against stationary phase E. coli . Cinnamon bark has a long history in western medicine to soothe aching joint and numb pain and its bioactivity against bacteria, fungus, inflammation, cancer and diabetes has been described [25]. Here, we showed that Cinnamon bark oil had a low MIC (0.03%) and remarkable anti-persister activity.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Additionally, we found Cinnamon bark, Syzygium aromaticum, Allspice and Bandit "Thieves" showed excellent activity against stationary phase E. coli . Cinnamon bark has a long history in western medicine to soothe aching joint and numb pain and its bioactivity against bacteria, fungus, inflammation, cancer and diabetes has been described [25]. Here, we showed that Cinnamon bark oil had a low MIC (0.03%) and remarkable anti-persister activity.…”
Section: Discussionmentioning
confidence: 59%
“…Clove bud is a natural product with great potential use in food preservation [30]. Along with Cinnamon bark, Cinnamon leaf and Clove bud showed strong antibacterial activity presumably due to the major component eugenol [25, 29, 30]. Some studies demonstrated that eugenol could denature cellular proteins and change cell membrane permeability when interacting with growing bacteria [30], which could indicate it has similar effect against stationary phase bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…C. zeylanicum is used as part of Ayurvedic medicine as a remedy for a variety of digestive, respiratory, and gynecological symptoms . Various pharmacological effects of cinnamon have been reported including antibacterial, antifungal, antioxidant, antidiabetic, anti‐inflammatory, and immunomodulatory effects. When administered orally in experimental allergic encephalomyelitis in mice, cinnamon powder suppressed the expression of iNOS and IL‐1β in vivo in the spinal cord and cerebellum, suggesting anti‐inflammatory effects .…”
Section: Resultsmentioning
confidence: 99%
“…Cinnamaldehyde, the most abundant components of the cinnamon essential oil, either used alone or in combination exhibited potent antibacterial and antifungal activities (Utchariyakiat et al 2016;Friedman 2017;Firmino et al 2018;Garcia-Salinas et al 2018). The anti-inflammatory properties and wound healing application of cinnamon oil for soothing the pain resulted from microbial infection and inflammation have been identified (Han and Parker 2017). Additionally, cinnamon oil has been reported to be safe for treating oral candidiasis (Oliveira et al 2014) and Helicobacter pylori-causing gastritis in humans (Nir et al 2000).…”
Section: Introductionmentioning
confidence: 99%